(3CUhd JQcjH GdCOhjIs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3Rjf GdYGHOjf Hf eMeO HGHG afcQI s)
(3ChdgG (B:s
(3bGd GdTjN GdaGVd eMeO Hf Ydi GdSeQbfOi Ef GdhGLH Ydi cd Pi dH Cf jJbQH Edi Gddg hjJhSd Edjg hCMSf GdhSGFd hCLhO GdPQGjY EeJKGd GdChGeQ hGdfhGgi s
(3BNQgG (B:s
(3hjJQc MJi jLa hGddg GdgGOi Edi MbGFb CSQGQg , GdcGTa Yf GZWjI GdLGgdI HCfhGQg Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdfSNI HgG MhGTs
(3fSNI QGHYI ef GdbSe GdKGdK ef GdfLjHjGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
Keywords: (3GdWHs